2009
DOI: 10.1039/b913635e
|View full text |Cite
|
Sign up to set email alerts
|

FTIR study on the light sensitivity of the [NiFe] hydrogenase from Desulfovibrio vulgaris Miyazaki F: Ni–C to Ni–L photoconversion, kinetics of proton rebinding and H/D isotope effect

Abstract: The light-induced Ni-C to Ni-L transition results in the dissociation of a hydrogenic species, originating from the dihydrogen splitting at the active site. Back conversion in the dark to form Ni-C was investigated by studying the rebinding kinetics of this ligand in protonated (H(2)/H(2)O) and deuterated (D(2)/D(2)O) samples using time resolved FTIR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 20 publications
5
46
1
Order By: Relevance
“…100 cm −1 as observed for [(dppe)Pt(pdt)Fe(CO) 3 ] +/0 , a Pt II Fe I /Pt II Fe 0 couple. 21 For the Ni-L state of the [NiFe]-hydrogenases, the values of ν̃ CO range from 1911 ( Desulfovibrio vulgaris Miyazaki F) 34 to 1862 cm −1 ( Aquifex aeolicus ) (Table 4). 26,35 …”
Section: Resultsmentioning
confidence: 99%
“…100 cm −1 as observed for [(dppe)Pt(pdt)Fe(CO) 3 ] +/0 , a Pt II Fe I /Pt II Fe 0 couple. 21 For the Ni-L state of the [NiFe]-hydrogenases, the values of ν̃ CO range from 1911 ( Desulfovibrio vulgaris Miyazaki F) 34 to 1862 cm −1 ( Aquifex aeolicus ) (Table 4). 26,35 …”
Section: Resultsmentioning
confidence: 99%
“…A light-minus-dark FTIR difference spectrum for the D. vulgaris MF hydrogenase is shown in Figure 6 c. Rapid scan kinetic measurements (Figure 7 a) showed that rebinding of the hydride ligand as a proton is a first-order process. [124] The determined activation barrier is 46 kJ mol…”
Section: Light-induced Structural Changes In the Active Sitementioning
confidence: 99%
“…In this case, the Ni-Fe bond would be present transiently, because the state containing this bond would be generated in aqueous solvent where [H + ] is ~ 10 −7 M, such that the rate of protonation may be exceedingly fast. Interestingly, the Ni-L state of the enzyme, obtained by exposing frozen solutions in the Ni-C state to light, may contain the Ni I -Fe II bond after the bridging proton dissociates [37]. Perhaps during catalysis, Ni-L may form transiently, converting rapidly to Ni-C upon protonation (Figure 3, bottom).…”
Section: 4 Evidence For M-m Bonds In Metalloenzymesmentioning
confidence: 99%